THE IMPACT OF THE E-LKPD ASSISTED DISCOVERY LEARNING MODEL ON STUDENT LEARNING OUTCOMES OF EFFORT AND ENERGY - Basori, Muhammad; Noor, Azman Mohd. (SYNTIFIC, 2025)
Background. In the current era of digital education, enhancing students’ engagement and conceptual understanding in physics remains a challenge. Traditional teaching methods often lack the interactive components necessary for deep learning. Research Purpose. This study aims to determine the impact of the E-LKPD-assisted discovery learning model on students' learning outcomes of effort and energy. Research Method. At SMA Negeri 1 Medan, the study was carried out. This kind of study uses a pretest-posttest control group design and is quasi-experimental in nature. With 36 students in each of the experimental and control classes, cluster random sampling was the sampling method employed in this investigation. In the experimental class, the Discovery Learning model was used with the help of E-LKPD, whereas in the control class, traditional learning was used. The pupils in grades X-3 and X-4 served as the study's subjects. A learning exam consisting of fifteen multiple-choice questions served as the tool. Findings. A pretest result in an average pretest score of 48.1 for the experimental class and 45.6 for the control class. Normality and homogeneity tests on the pretest data indicated that both classes' data were normally distributed and homogeneous. The two-tailed t-test resulted in a value of tcount < ttabel = = 0.97 < 1.994, indicating that the initial critical thinking ability of the experimental and control classes was the same. After the different treatments, a posttest was conducted for both classes, which resulted in an average posttest score of 76.5 for the experimental class and 63.5 for the control class. Normality and homogeneity tests on the posttest data showed that both classes' data were normally distributed and homogeneous. The one-tailed t-test resulted in tcount < ttabel = = 4.860 > 1.666, so the alternative hypothesis (Ha) was accepted. Conclusion. Students’ learning results on the subject of effort and energy are significantly impacted by the usage of Discovery Learning with E-LKPD assistance.